Reflexões sobre raça e racismo em sala de aula: uma pesquisa com duas professoras de inglês negras - SILVA, Paula de Almeida (2009)
The present study is a recherche-formation accomplished by two graduating black female English teachers and supported by a researcher. This study attempted to investigate the meaning of race and racism for these teachers and how these two themes were approached in their lessons. Furthermore, it attempts to investigate the consequences of the research for the life of these teachers. In order to carry out this work studies about four themes were used as theoretical background: race and racism (CARNEIRO, 2002; FOUCAULT, 1999; GUIMARÃES, 1999; Hooks, 1992; MOORE, 2007; MUNANGA, 2004; STEPAN, 2005; SALES JR., 2006); language (AUSTIN, 1975; WEEDWOOD, 2002; RAJAGOPALAN, 2003; BAKHTIN, 1888); critical teaching and teaching education (GOMES, 1995; GONÇALVES E SILVA, 2006; FREIRE, 1993; MOITA LOPES, 2002); and recherche-formation (JOSSO, 1999; 2000; 2004). The results show that, by participating in the meetings promoted by the research, which focused on their life s history and their classes, the teachers reflected more profoundly about race and racism in Brazil, showing that recherche-formation, based on the participants narratives, helped to better understand how personal and professional relations are intertwined by race and racism. Based on their own reflections, the teachers developed activities addressing the two themes in a way that reflecting with students was also undertaken. The data analysis portrays that the teachers have also become researchers and have adopted the approach of these themes in their classrooms as a permanent agenda, and changed their perceptions as black women.